Simulation-Based Training for interprofessional and patient-centered communication skills:: A Community-Based Approach for nursing and medical students - Suragarn, Usar; Luck, George R.; Goldstein, Mark; Jacomino, Mario; Pfaff, Glenn (Health Workforce Education Journal, 2023)
Educational institutions have a responsibility to produce a future healthcare workforce and prepare students to develop interprofessional competencies. This pilot study describes how a college of medicine responded to the need for interprofessional education by providing a simulation-based learning program available to medical and nursing students in the community as a routine part of their education. The simulation-based learning activities combined the Interprofessional Education Collaborative Core Competencies for professional communication practice and patient-centered communication skills. This simulation-based interprofessional learning program (Sim-ILP) consists of two sessions. The first session was a three-hour module designed specifically for nursing students to identify the differences in nurse-to-physician communication patterns and changes in the patient condition report. The second session was a four-hour module where nursing and medical students engaged with standardized patients in a primary-care setting, and human patient simulators in hospital settings. The comments from the program evaluation and the video-assisted verbal debriefing were positive. The medical students (n=16) and nursing students (n=16) learned how to develop a cooperative team effort across both professions, communicated shared decision-making plans of care with patients, and developed a collaborative care plan. The students recognized the importance of patient-centered communication to provide effective patient care, and the values of collaboration and shared decision-making by interprofessional teams. Simulation-based interprofessional learning program can be an effective strategy for shifting the way healthcare students communicate and collaborate to deliver patient-centered care to patients, families, and communities.